Pengaruh Current Ratio dan Return on Asset terhadap Return Saham - Bau E; Handani Handani; Mulyono Mulyono (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
This study aims to analyze the effect of financial ratios, specifically the Current Ratio (CR) and Return on Assets (ROA), on stock returns of food and beverage subsector companies listed on the Indonesia Stock Exchange (BEI) during the period 2022–2024. The approach used is quantitative with a descriptive method and multiple linear regression analysis, along with classical assumption tests to ensure data validity. The sample consists of 18 companies that meet the purposive sampling criteria based on the availability of complete financial statements, observation periods, and no losses. Data were obtained from annual financial reports available on the official BEI website and individual companies. The analysis results show that, simultaneously, both Current Ratio and Return on Assets have a positive and significant effect on stock returns, indicating that liquidity and profitability are important factors affecting investment returns in this sector. Partially, ROA has a significant positive effect on stock returns, while the effect of CR is positive but not significant. These findings provide strategic implications for companies in managing financial aspects and for investors in making investment decisions based on financial indicators. This study is expected to contribute to the development of knowledge in corporate finance.